2020
DOI: 10.21203/rs.2.21325/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developing a roadmap to improve trial delivery for underserved groups: results from a UK multi-stakeholder process

Abstract: Background Participants in clinical research studies often do not reflect the populations for which healthcare interventions are needed or will be used. Enhancing representation of underserved groups in clinical research is important to ensure that research findings are widely applicable. We describe a multicomponent workstream project to improve representation of underserved groups in clinical trials. Methods The project comprised three main strands: 1) a targeted scoping review of literature to identify prev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Common eligibility criteria clinical exclusions, as highlighted with overlap by recent FDA guidance [17,18] and those relevant to breast cancer clinical trials from the INCLUDE 2017 framework [2], as requiring revision in order to enhance clinical trial diversity, were assessed (Table 1). Examples of INCLUDE 2017 framework underserved groups deemed not suitable for inclusion in this study included ''looked after children,'' ''carers,'' ''military veterans,'' ''those in full-time employment,'' ''rare diseases,'' and ''people who do not attend regular medical appointments'' as this data was either not relevant to breast cancer trials (''looked after children'' and ''rare disease'') or this data was not captured in the patient characteristic section of the trials assessed.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Common eligibility criteria clinical exclusions, as highlighted with overlap by recent FDA guidance [17,18] and those relevant to breast cancer clinical trials from the INCLUDE 2017 framework [2], as requiring revision in order to enhance clinical trial diversity, were assessed (Table 1). Examples of INCLUDE 2017 framework underserved groups deemed not suitable for inclusion in this study included ''looked after children,'' ''carers,'' ''military veterans,'' ''those in full-time employment,'' ''rare diseases,'' and ''people who do not attend regular medical appointments'' as this data was either not relevant to breast cancer trials (''looked after children'' and ''rare disease'') or this data was not captured in the patient characteristic section of the trials assessed.…”
Section: Methodsmentioning
confidence: 99%
“…Recently the New England Journal of Medicine editorial, ''Striving for Diversity in Research Studies'', highlighted this issue [4] and introduced a requirement for ''a supplementary table that provides background information on the disease, problem, or condition and the representativeness of the study group'' that must be part of all publications in the NEJM from January 1st, 2022. INCLUDE, a 2017 initiative from the UK's National Institute of Health Research (NIHR), has defined and identified underserved groups in clinical trials and accompanying barriers to recruitment [2]. Examples of underserved groups listed by this framework include the elderly (particularly those O75 years of age), ethnic minorities, the socioeconomically deprived, pregnant and lactating women, the lesbian, gay, bisexual, transgender, queer, and others (LGBTQþ) community, people living in rural areas and those with comorbidities, including disability, mental health conditions or cognitive impairment, among others [2].…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 99%
See 3 more Smart Citations